2015
DOI: 10.1093/abbs/gmv036
|View full text |Cite|
|
Sign up to set email alerts
|

Over-expression of recombinant proteins with N-terminal His-tag via subcellular uneven distribution in <italic>Escherichia coli</italic>

Abstract: Specific tags with defined amino acid residues are widely used to purify or probe target proteins. Interestingly, the tagging system occasionally results in an increase of the recombinant protein expression in vivo. Here, we systematically examined this phenomenon using a poly-histidine (His)-tag fused to N- or C-terminal region of green, red, and blue fluorescent proteins by quantification and uneven distribution in cytoplasm of Escherichia coli. This effect was further supported by the distinct over-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…These results suggested that mutagenesis of only terminal regions could effect on the translation rate properties of difficult-to-express proteins [25]. In addition, the resulting bias in the length and sequence of the selected mutants strongly supported the view that histidine-enriched oligopeptide sequences in the N-terminal region of recombinant proteins in E. coli favor a relatively high expression level and solubility, as observed in our previous report [23]. As expected, the elongated peptides at their N-terminal regions were not predicted to form a distinct secondary structure.…”
Section: Screening and Sequence Analysis Of Recombinant Proteins Withsupporting
confidence: 84%
See 1 more Smart Citation
“…These results suggested that mutagenesis of only terminal regions could effect on the translation rate properties of difficult-to-express proteins [25]. In addition, the resulting bias in the length and sequence of the selected mutants strongly supported the view that histidine-enriched oligopeptide sequences in the N-terminal region of recombinant proteins in E. coli favor a relatively high expression level and solubility, as observed in our previous report [23]. As expected, the elongated peptides at their N-terminal regions were not predicted to form a distinct secondary structure.…”
Section: Screening and Sequence Analysis Of Recombinant Proteins Withsupporting
confidence: 84%
“…PCR-based elongation mutagenesis was performed and the resulting pool was screened for mutants with improved expression and solubility, based on the emitted fluorescence of the fused reporter mCherry. In this procedure, we arbitrarily enriched histidine codons in the wobble sequence to avoid proteolysis and to facilitate protein purification via metal-affinity column, based on a recent report [23].…”
Section: Screening and Sequence Analysis Of Recombinant Proteins Withmentioning
confidence: 99%
“…pTrc99a (Pharmacia Biotech, Uppsala, Sweden) was used as the backbone plasmid to construct the pTB vector without any factors for gene expression. pQE30-1767 [14], pTrc99a-SmGlu [15], pMal-c2x Phusion (New England laboratory, Hitchin, UK), and pGFPuv (Clontech, Mountain view, CA, USA) were used as templates for PCR amplification of esterase 1767, β-glucosidase, maltose binding protein, and green fluorescence protein, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To test the feasibility of novel expression systems, four genes encoding MBP, GFPuv, esterase 1767 [14], and SmGlu [15] were amplified by PCR using appropriate primer sets from pMal-c2x, pGFPuv, pQE30-1767, and pTrc99a-SmGlu, respectively (Table 1). The PCR-amplified genes were treated with appropriate restriction enzymes and then ligated with the corresponding vector digested with the same restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…However, the optimal length of this linker varies with every riboswitch and each new genetic context, leading to the formation of fusion proteins of varying length. An N-terminal fusion will often affect the stability, solubility, localization or functionality of the protein of interest-especially in the case of enzymes (Chant et al 2005;Park et al 2015). allowed them to successfully enhance the modularity of riboswitches and circumvent the inclusion of a 5 0 fusion, increasing protein production by $ 1000 fold.…”
Section: Limitations Of Synthetic Riboswitches and Potential Mitigationsmentioning
confidence: 99%